Celecoxib, a selective cyclooxygenase‐2 inhibitor, reduces level of a bone resorption marker in postmenopausal women with rheumatoid arthritis. (23rd May 2013) - Tsuji, Shigeyoshi; Tomita, Tetsuya; Nakase, Takanobu; Hamada, Masayuki; Kawai, Hideo; Yoshikawa, Hideki
Abstract Aim Celecoxib (CEL), a selective cyclooxygenase‐2 (COX‐2) inhibitor, has been reported to suppress osteoclastogenesis in vitro, reduce levels of bone resorption markers in ovariectomized (OVX) mice, and prevent bone destruction in rheumatoid arthritis (RA) model mice; however, no clinical data has been reported. Here, we prospectively evaluated the changes in bone turnover markers in RA patients who switched from nonsteroidal anti‐inflammatory drugs (NSAIDs) to CEL, to examine the effects of selective COX‐2 inhibitor on bone metabolism. Methods RA patients who had been treated with NSAIDs for more than 12 weeks were switched to CEL (400 mg/day) without any other changes in previously prescribed medications. Urinary type I collagen cross‐linked N‐telopeptide (uNTX), serum bone alkaline phosphatase (BAP), C‐reactive protein (CRP), erythrocyte sedimentation rate (ESR) and matrix metalloproteinase‐3 (MMP‐3) were evaluated before switching to CEL and 16 weeks later. Results Significant reductions in uNTX, a bone resorption marker, were observed in 60 female patients (P = 0.042), especially in 52 postmenopausal women (P = 0.033). However, uNTX level did not significantly change in premenopausal women or in men. There were no significant changes in BAP, a bone formation marker. CRP significantly decreased (P = 0.007), while ESR and MMP‐3 were unchanged. Conclusion CEL reduced the levels of a bone resorption marker in postmenopausal RA patients, suggesting that this drug may attenuate the accelerated osteoclastic bone resorption associated with menopause.